dada a funcao f:R e R definida por f(x)= -3x+1 l,determine f-2:
a:f(-2)=3
f (-2)=4
f(-2)=6
f(-2)=7
Soluções para a tarefa
Respondido por
1
Dada a funcao f:R e R definida por f(x)= -3x+1 l,determine f-2:
f(x) = - 3x + 1
f(-2) = - 3(-2) + 1
f(-2) = + 6 + 1
f(-2) = 7
a:f(-2)=3
f (-2)=4
f(-2)=6
f(-2)=7 ( resposta)
f(x) = - 3x + 1
f(-2) = - 3(-2) + 1
f(-2) = + 6 + 1
f(-2) = 7
a:f(-2)=3
f (-2)=4
f(-2)=6
f(-2)=7 ( resposta)
Perguntas interessantes
Espanhol,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás